Pelatihan Dasar Pengolahan Minuman dan Perhitungan Harga Jual di Panti Asuhan Nurul Haq - Lutfi Hendriyati; Hery Krestanto (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The purpose of holding this community service is to provide knowledge about beverage processing and provide knowledge about calculating selling prices. This training is intended for students at the Nurul haq orphanage who wish to become entrepreneurs and deepen their knowledge of beverage processing. The method used in processing drinks and calculating the selling price is using the Lecture and Hands-on Practice method. Beverage Processing Beverage Processing Training activities make 4 drinks namely Blue Sky On The Snow, Sweet Purple, Strawberry Milkshake and Strawberry Squash Mint. In this hands-on practice, participants are invited directly to participate in preparing drinks accompanied by Yogyakarta Tourism Academy students. The selling price is calculated using the Cost Approach Method. Training participants/community can use other methods that are considered easy to use.